Regionalization of Cacao (Theobroma cacao L.) in Colombia - González-Orozco, Carlos E.; Pesca, Allende (Frontiers in Sustainable Food Systems, 2022)
A detailed description and up to date biogeographic regionalization of cultivated cacao (Theobroma cacao L.) are lacking in Colombia. Here we propose a new biogeographical regionalization of cultivated cacao for Colombia. We used spatial partitioning, geospatial mapping of macro/microclimate variables and a hierarchical area taxonomy classification to describe, define and propose the biogeographical regions of cultivated cacao. The cacao regions were identified from distributions of 4,974 cocoa producing farms across Colombia. Our proposed regionalization comprises four regions (north-eastern, north-western, south-western, east), 31 sub-regions and 54 provinces. Solar radiation, precipitation, and soil temperature seasonality best explained the biogeographical regions. Rivers networks helped explain the differences at the sub-regional and provinces level. Our results indicate that biogeography is a strong indicator of cacao's agricultural expansion across the different growing regions in Colombia. This up-to-date biogeographical classification could be a useful tool for agricultural planning of cacao in Colombia. Particularly, the baseline information provided might be of use on the development of denominations of origin for cacao.